The Court of Justice of the Economic Community of West African States as a Constitutional Court Member States obligations resulting from the Court´s rulings - Bado, Kangnikoé (Nomos Verlagsgesellschaft mbH & Co. KG, 2019)
One of the major innovations made by the Economic Community of West African States (ECOWAS) is the unequivocal granting of a supranational role to the Court of Justice of the organisation. However, its human rights mandate has led to real and potential tensions within the ECOWAS legal order. The tensions stem from the legal force of judgements of constitutional courts of member states and the admissibility of individual petitions before the Court. This work identifies some deficiencies in the current regime of the human rights mandate of the Court. Gaps exist at the level of the member states' constitutional order, as well as at the community level. The supranational competence of the jurisdiction must be implemented by the possibility of ordering concrete measures to be taken by states for the reparation of human rights violations. Innovative solutions are suggested in this work in order to fill procedural and substantial gaps in the protection system established in West Africa.